Driving Forces Behind European Commercial Real Estate Prices Prior to a Sharp Fall in Prices - Marius Hagen; Frank Hansen (Norges Bank, 2018)
What factors have driven commercial real estate (CRE) prices upwards prior to a sharp fall in prices? We study this question by identifying turning points in CRE for a dataset covering the prime office segment in 58 cities in Europe. CRE prices are decomposed into rents and CRE yields. Our results show that the increase in rents was the main driver behind the rise in CRE prices before peaks in the period 1980 to 2003. In the period 2004 to 2016, the decline in CRE yields was the main driver and was partly caused by a general downward trend in European CRE yields before the global financial crisis. A significant part of the decline is still left unexplained after controlling for factors such as the risk-free rate, the risk premium and city-specific effects. The reduction in CRE yields caused by the residual and the time dummies was likely driven by a change in omitted variables such as time variation in access to credit, capital requirements, the expected long-run rent growth rate and/or CRE specific risk premiums.
hdl:11250/2558911
Keywords: 330